Membangun Jiwa Wirausaha Sejak Dini: Implementasi Penguatan Kewirausahaan Melalui Mata Pelajaran di SMA As-Siddiqy - Puryantoro Puryantoro; Muhamamd Yusuf Ibrahim; Ika Wahyuni (Lembaga Penjaminan Mutu Universitas Abdurachman Saleh Situbondo, 2025)
The purpose of this community service activity with the theme of entrepreneurship is to encourage students to improve their skills and develop their own entrepreneurial potential. At SMK As-Siddiqy in Situbondo Regency, the program was run using the question and answer learning method, an interactive approach that combines material presentation with question and answer sessions. In addition, to measure participants' understanding, pre- and post-tests were conducted to evaluate their understanding. The results of the activity showed a 42% increase in students' understanding and ability to create creative business concepts that fit the needs of the market. market. The active involvement of participants and the interactive methods used influenced the success of the program. Continued mentoring is needed to address participants' lack of experience in implementing creative ideas. This activity confirms that practice-based entrepreneurship education is very important to foster students' confidence as future entrepreneurs.